A medicina homeopática : avaliação de serviços - Novaes, Ana Rita Vieira de (2007)
This research aims to analyze the services as well as its homeopathic practice at the Public Health Service in Vitória, ES and make a proposal to build evaluation parameters for homeopathy at SUS. In order to achieve this goal it is necessary to know the homeopathic services, homeopaths, managers and users examining their interpersonal relationships. It deals with an exploratory study having as reference the triangulation methodology which means combining and crossing multiple points of view, the vision of many people and the usage of a variety of data techniques. The first stage aims to make situational diagnoses of the services and know the structural, organizational, management, administrative aspects and how they work. The second and third stages intend to consolidate the knowledge of the social actors and understand the process of the work and then all the information is articulated as well as crossed identifying the main themes which answer the proposed questions. The ideas and information from the interviews are systematically evaluated, as a way to achieve a deep comprehension of the process. The quantitative data is classified and tabulated, and from the descriptive analyses the percentage through EPI-INFO and/or SSPS are taken, shown in graphs and charts. The results are described in chapters giving details of the main aspects of the homeopathic practice, supported by a theoretical reference and the interviewers´ perceptions. The first chapter focuses on the principles and fundaments of the homeopathy, giving a historical retrospective, showing the institutionalization of the homeopathy in Brazil, the process of implementation in the public service and the main contributions it *gives as a model*. Then, the homeopathic service is detailed, including the analyses of the records. The third chapter deals with the aspect of medical education, the peculiarities of the homeopaths and users and doctor-patient relationship. Chapter fourth discusses the present stage of communication in relation to homeopathy and examines the interrelation in the public area. It also attempts to give the consonance of homeopathy with the principles and rules of the Brazilian Health Public System. The last chapter a proposal of evaluation for homeopathy is made by means of the discussion of the parameters which can distinguish this rationality. It is concluded that, despite having been implemented in Vitória for fifteen years and the increasing interest, it is of difficult access. It is also observed that many structural and organizational problems, specially lack of homeopathic medication as well as investment of the public power in this kind of medicine. The users and managers are considerably unaware of the SUS and the homeopathic culture, restricting its institutional inclusion. The participation of the social control is practically inexistent, preventing the right of citizenship in the choice of which treatment and as an instrument of a popular influence. In this way, the universal access is jeopardized due to the low number of homeopaths at SUS, despite the agreement with principle of integrality and the recognition of homeopathy as a humanized medicine which values the relationship between doctor and patient and the human being as a whole.